(untitled) (Research, Society and Development, 2022)
The purpose of this Scope Review Protocol, which follows the recommendations of the JBI manual, is to map existing technologies aimed at preventing suicide and promoting adolescent mental health. Bibliographic materials that address the technologies of prevention anpromotion of Mental Health (concept) aimend at adolescents (population) around the world (context) will be eligible. A detailed and individual Search strategy will be used in the following databases: Pubmed, PsycInfo, Medical Literature Analysis and Retrieval System (Medline), via the Virtual Health Library (BVS), Scopus and Latin American and Caribbean Literature in Health Sciences (LILACS) via BVS. The Search in gray literature will be done on the Google Scholar website and websites of the Ministry of Health (MS), WHO, PAHO, UNICEF, Brazilian Society of Psycology, Brasilian Society of Psychiatry, Federal Council of Psychology. The seletion process will be carried out by two independente reviewers who will screen the titles and abstracts, read the full texts and extract data from the included material, and disagreements will be resolved by consensus or by the third reviewer. From the extracted data, a descriptive synthesis of the studies will be classified into conceptual analysis categories based on the Thematic Category Analysis, based on Bardin`s contente analysis.